2020
DOI: 10.5455/javar.2020.g448
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of IL-6 and IL-10 in the testicular tissue of testicular dysfunction rat treated with secretome

Abstract: Objective: This study was carried out to find out the immunolocalization of Interleukin 6 (IL-6) and Interleukin 10 (IL-10) in the testicular tissue of testicular dysfunction rat treated with secretome from human umbilical stem cells. Materials and methods: Rats were induced with cisplatin for testicular dysfunction condition. After that, the rats were grouped into two categories and were treated with secretome at 0.2 and 0.5 ml/kg BW once every week for 4 weeks. One we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Spermatogenesis occurs as a result of a complicated interaction between spermatogenic cells and testicular interstitial cells, which is facilitated by an appropriate environment. These include endocrine, paracrine, and autocrine systems [ 7 ]. The secretome contains basic fibroblast growth factor, a growth factor that promotes Sertoli cell proliferation in the testes and also stimulates Sertoli cells to make glutatonin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spermatogenesis occurs as a result of a complicated interaction between spermatogenic cells and testicular interstitial cells, which is facilitated by an appropriate environment. These include endocrine, paracrine, and autocrine systems [ 7 ]. The secretome contains basic fibroblast growth factor, a growth factor that promotes Sertoli cell proliferation in the testes and also stimulates Sertoli cells to make glutatonin.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, secretome has been studied as a potential therapeutic paradigm for central nervous system neurodegenerative diseases [ 6 ]. Secretome infusion appears to be able to modulate certain cytokines such as IL6 and IL10 during the testicular regeneration process [ 7 ]. It is not limited to soft organs; it has been demonstrated that secretome therapy promotes osteogenic differentiation in animals with faulty osteogenesis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Histone Post-Translational Modifications (PTM), as well as histone-writers and reader proteins are critical regulators of the gene expression programs in both the germline and the zygote. From C. elegans to the mouse, several PTMs in sperms and oocytes including mono and di-methylations of histone H3 at lysine 4 (H3K4me1/me2) and trimethylation of histone 3 at lysine 9 (H3K9me3), are retained at genomic regulatory elements (118), imprinted regions and miRNA clusters (119,120). Disruptions in the histone retention regions in sperms produced by environmental stimuli can transgenerationally persist up to the third generation (121)(122)(123).…”
Section: Epigenetic Inheritance Of Environmental Experiences: Can Bacteria Modify the Germline?mentioning
confidence: 99%
“…Testicular tissues were collected one week after the first, second, third, and fourth injection of mesenchymal stem cells-conditioned medium. Testicular tissues were fixed in Bouin's solution for 24 hours, embedded in paraffin, sectioned to a thickness of 5 µm, and stained with the immunological method (Prihatno et al, 2020) to visualize the immunoreactivity of HSD3B1, HSD17B1, and P450scc.…”
Section: Sample Collectionmentioning
confidence: 99%
“…The slides were washed in Phosphate Buffer Saline (PBS) for five minutes, then repeated three times. Immunoreactivity was visualized with rabbit Diaminobenzidine (DAB) Detection IHC Kit (Fine Test, Wuhan Fine Biotech Co., Ltd., China) (Prihatno et al, 2020). After that, the slides were incubated overnight at 4 0 C with HSD3B1 polyclonal antibody (1: 200, MBS2530192, Mybiosource, USA), HSD17B1 polyclonal antibody (1:400, A10839, ABclonal, USA), and Cytochrome P450scc Enzyme polyclonal antibody (1:500, AB1244, MilliporeSigma, USA).…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%